2016
DOI: 10.18203/2320-1770.ijrcog20164663
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of asymptomatic bacteriuria in early pregnancy

Abstract: Background: Bacteriuria is a major risk factor for developing symptomatic urinary tract infection which is associated with significant maternal and fetal risks. Various studies have put a prevalence of asymptomatic bacteriuria between 2-10% in pregnancy. Maternal and fetal complications like gestational hypertension, anaemia, premature delivery, IUGR, and low birth weight are commonly associated with pyelonephritis which occurs as a result of undiagnosed or inadequately treated infections of the urinary tract.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 7 publications
3
21
0
1
Order By: Relevance
“…The women of LD group had 14 times greater Odds of developing UTI in pregnancy when compared to ED group in the present study. Not only that, previous history of UTI was shown as a definite risk factor for ASB by Tahir S et al 23 The present study shows that women in LD group had 6.9 times greater Odds of developing gestational HTN or Preeclampsia similar to the findings of Radha S et al and Yu FN et al 21,24 However, no case of Gestational HTN or Preeclampsia was noted by Nkwabong E et al in their study. 25 No case of acute pyelonephritis occurred in any of the three groups in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The women of LD group had 14 times greater Odds of developing UTI in pregnancy when compared to ED group in the present study. Not only that, previous history of UTI was shown as a definite risk factor for ASB by Tahir S et al 23 The present study shows that women in LD group had 6.9 times greater Odds of developing gestational HTN or Preeclampsia similar to the findings of Radha S et al and Yu FN et al 21,24 However, no case of Gestational HTN or Preeclampsia was noted by Nkwabong E et al in their study. 25 No case of acute pyelonephritis occurred in any of the three groups in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…20 A lower prevalence rate of 8.4% and 8.25% was obtained in a study by Lavanya SV et al and Radha S et al respectively. 10,21 This may be because most of the patients in our study were rural women with lower level of education and socioeconomic status. Jain V et al and Paari P et al observed a higher prevalence of 16.9% and 21.1% respectively.…”
Section: Discussionmentioning
confidence: 86%
“…E. coli is the most common isolate in ASB as it was also confirmed in a prospective study in Odisha state, India and in Abuja (56.%) [19][20][21][22][23]. CoNS is one of isolated uropathogens [25]. In another study CoNS was second most common (16.8%) after E. coli (58.96%) [26].…”
Section: Discussionmentioning
confidence: 55%
“…The bacteria were more susceptible to gentamycin, ceftriaxone and ciprofloxacin but resistant to nitrofurantoin and ampicillin. Nitrofurantoin is a widely recommended antibiotic for ASB treatment in pregnancy and it is associated with 80% cure rate with a 5 to 7 day course [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Suggested first line treatment include amoxil, nitrofurantoin and oral cephalosporins and gentamycin and ceftriaxone for staphylococcus and pseudomonas [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were claimed by Radha et al, where the incidence of preeclampsia was found to be 6.1%. 28 The higher incidence of preeclampsia in group I women can be attributed to increased maternal cytokines found in ASB may reflect vascular endothelial function which in turn leads to preeclampsia. 29 The incidence of anaemia was found to be high (14.7%) in group I pregnant women as compared to group II (4.5%).…”
Section: Discussionmentioning
confidence: 99%